Impact of Tourism Development In Urug Traditional Village, Bogor - sheva Aulia; Liliana Dewi (CV ODIS, 2022)
The research aims to identify the impact of tourism on the culture of the Urug traditional village; the data analysis technique used the qualitative method where the research carried out observation and interviews and the SWOT technique. The resulting study is the Urug traditional village maintains culture, such as traditional ceremonies such as Muludan, Seren Taunan, activities Sedekah Bumi and traditional houses. They still adhere to the rules of tradition and custom that are arranged to have pits and rice granaries and the shape of a house that has characteristics typical Sundanese or called Julang Ngapak where the traditional building is in the form of a house on stilts.